Moral grounds and social norms of safe prosocial behaviour of young people - P. A. Kislyakov; E. A. Shmeleva; M. O. Aleksandrovich (Образование и наука)
Introduction. In the current situation of socio-economic development and digitalisation of society, the question of moral standards is becoming particularly relevant. Individualism, values of self-actualisation, enrichment and autonomy are strengthened in the youth environment, and values of civic participation and moral identity are not developed. In this regard, prosocial attitudes aimed at providing selfless assistance to a person or society as a whole are popularised among young people at the state level.The aim of the present research is to identify the dominant moral grounds and norms of safe prosocial behaviour of young people.Methodology and research methods. The current research is based on the theory of moral grounds, the theory of social norms of prosocial behaviour, and the theory of social and psychological security. The following psychodiagnostic methods were applied: “Diagnostics of the Level of Moral and Ethical Responsibility of the Individual” (by I. G. Timoshchuk), “Moral Foundations Questionnaire” (by J. Haidt et al., in the adaptation of O. A. Sychev et al.); “Scale of Altruism” (by F. Rushton, in the adaptation of N. V. Kuhtova), “Social Norms of Prosocial Behaviour” (by I. A. Furmanov, N. V. Kuhtova). The obtained empirical data were processed using percentage analysis, the Kraskel-Wallace criterion, the Pearson correlation analysis, and linear regression analysis (the step method). Calculations were done employing the SPPS 22 statistical program package.Results and scientific novelty. The conducted research has shown that moral and ethical responsibility and prosociality among young people are formed at a sufficient level. The norms of care, justice, and social responsibility are the dominant moral grounds and norms of prosocial safe behaviour of young people. Despite the fact that assistance is mainly dictated by pragmatic motives, safe prosocial behaviour of young people is predicted by compliance with group rules and the absence of selfish expectations of reciprocity.Practical significance. The identified relationships allow for the prediction of the level of readiness of the individual to help and take care of the well-being of another person and society, depending on moral norms and norms of prosocial behaviour. In the process of personal and professional development and spiritual and moral development of young people, it is advisable to use situational modelling aimed at solving moral dilemmas and forming attitudes to prosocial behaviour within the framework of the humanities cycle.